Anticipated social remittances: knowledge transfer among Sudanese and Egyptian students in Indonesia - Yasir Esam Osman Mohammed (CV. Literasi Indonesia, 2026)
International student mobility research has largely focused on movement from the Global South to the Global North, leaving South-South mobility, including Indonesia as a host destination, comparatively unexamined. This qualitative study investigates the anticipated social remittances of Sudanese and Egyptian postgraduate students in Indonesia: the knowledge, practices, and civic norms they expect to carry home. Drawing on data from ten participants (five Sudanese, five Egyptian) and reflexive thematic analysis, most were found already engaged in informal sharing, mainly via WhatsApp, though only some carried clear developmental intent rather than incidental cultural exchange. Anticipated extensions remained at the idea or informal-discussion stage, consistent with participants' early program stage, and nearly all insisted anything brought home would need local adaptation. Perceptions of home-country receptivity diverged by nationality: Egyptian participants described stable bureaucratic and cultural resistance, while Sudanese participants described a landscape reshaped by ongoing conflict, marked less by pessimism than by reordered priorities and, in one case, a new opening for the digital knowledge-preservation systems observed in Indonesia. The study extends social remittances theory to a temporary, credential-seeking population in a South-South context and offers early evidence on how home-country conditions, including active crisis, shape what students believe they can carry home.